Application of Modelling Building Information Modelling (BIM) in Bagendang Port Multipurpose Extension at Central Kalimantan - Yoni Galieh Kinanda; Ronny Durrotun Nasihien (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
BIM is a technology in the field of AEC that is able to simulate all information in a development project into a 3-dimensional model. In the world of construction in Indonesia BIM technology is still very minimal applied to the world of construction. he purpose of this final project is to design a planning model for the Extension of the Bagendang Port Multipurpose Pier in Sampit, Central Kalimantan using software from Aecosim. The results of this study show 3D results from the modeling of the Pier structure. This shows that BIM-based applications in planning and designing a building model can simplify the design analysis process.